ASSESSMENT OF DIETARY DIVERSITY AND NUTRITIONAL STATUS OF PREGNANT WOMEN IN ISLAMABAD, PAKISTAN - Ali, Fatima; Thaver, Inayat; Khan, Shahzad Ali (Journal of Ayub Medical College Abbottabad, 2014)
Background: Maternal under-nutrition is one of the most important causes of maternal morbidity and mortality, particularly in the developing countries. Maternal nutrition has direct association with foetal nutrition. This study aimed to identify dietary diversity and determine any relationship of dietary diversity with nutritional status of pregnant women belonging to different socioeconomic conditions in Rawalpindi Islamabad region. Methods: It was a cross sectional survey involving 350 pregnant women in their second and third trimesters, conducted in outpatient department of Maternal and Child health centre at Pakistan Institute of Medical Sciences (PIMS) Islamabad. A semi qualitative questionnaire was used that contained structured questions regarding socio-demographic features, socioeconomic status, nutritional status, and three day dietary recall. A second section comprising of questions regarding dietary perceptions was also Results: Out of total, 47% of pregnant women had normal pre-gestational BMI while, 22% were overweight, 17% obese, and only 12% of pregnant women were under weight. Similarly 28.1% were anaemic. Medium dietary diversity was observed in 89% of pregnant women, while only 5% showed low, and high dietary diversity. Dietary diversity was not associated with socio-demographic, or socioeconomic status of pregnant women. Even though weight gain during second (p=0.2 ) and third trimesters (p=0.049) had a positive relationship with dietary diversity, more than 74% of pregnant women gained less than recommended level of weight gain. No association could be proven between haemoglobin and dietary diversity (p=0.51). Conclusion: Dietary diversity is a good proxy indicator for micronutrient adequacy in pregnant women, however if quantity of food consumed is added it can give better indication of determinants of nutritional status of pregnant women. Keywords: Dietary diversity, Nutritional assessment, Pregnancy, Maternal nutrition